PELUANG PENGEMBANGAN FEROMON SEKS DALAM PENGENDALIAN HAMA ULAT BAWANG (Spodoptera exigua) PADA BAWANG MERAH - Yati Haryati; Agus Nurawan (Jurnal Penelitian dan Pengembangan Pertanian, 2009)
Prospect of pheromone sex development in controlling Spodoptera exigua on shallotThe main contraint in shallot cultivation is the high incidence of Spodoptera exigua. The pest causes significant damage on plant. To control the pest, farmers commonly use insecticides excessively. The intensive use of insecticides results in inefficiency and polluted environment. Therefore, breakthrough in controlling S. exigua is needed by using sex pheromone. Sex pheromone technology has been developed and tested in laboratory and in field and gave prospective results. Application of sex pheromone decreases the use of insecticide and production cost and increase farmers' income. Therefore, utilization of pheromone sex is prospective to be developed especially in shallot production centers and endemic for S. exigua.